Overexpression of Copines‐1 is associated with clinicopathological parameters and poor outcome in gastric cancer. Issue 11 (31st October 2022) - Yang, Jun; Wang, Yingjing; Ge, Rong; Jia, Xiupeng; Ge, Congshan; Cen, Youqing; Pan, Deng
Abstract: Background: Copines‐1 (CPNE1) is a soluble membrane‐binding protein that includes two tandem C2 domains at the N‐terminus and a C terminal A domain. Importantly, it is associated with the prognosis of various tumors, but there are only a few studies regarding the role of CPNE1 in gastric cancer (GC). This study aimed to explore the clinicopathological significance and prognostic potential of CPNE1 expression in GC. Methods: Data from the TIMER2.0 and UALCAN were analyzed to assess CPNE1 mRNA levels in GC. The prognostic role of CPNE1 mRNA was examined via the Kaplan–Meier plotter. CPNE1 protein expression in tumor tissues was analyzed via immunohistochemistry of clinical samples from 99 GC patients. The relationship of CPNE1 expression with clinicopathological parameters and overall survival (OS) was evaluated using Cox proportional hazards regression models and Kaplan–Meier survival curves. Results: Copines‐1 mRNA levels were higher in GC tissues than in adjacent normal tissue (ANT) ( p  < 0.05). Further, high CPNE1 mRNA expression indicated poor OS ( p  = 9.4 e‐10) and was significantly associated with first progression (FP) ( p  = 1.6 e‐06) and post‐progression survival (PPS) ( p  = 1.5 e‐12). In addition, CPNE1 protein expression was higher in GC tissues than in ANT ( p  < 0.0001). Moreover, CPNE1 high expression was significantly related to advanced tumor‐node‐metastasis (TNM) stage ( p  = 0.004), lymph node metastasis ( p  = 0.003), and vascular invasion ( p  = 0.001). Kaplan–Meier analysis showed that GC patients with high expression CPNE1 group had worse OS than low expression group ( p  = 0.003). Univariate analysis showed that age (hazard ratio [HR] = 1.992; 95% confidence interval [CI], 1.009–3.934; p  = 0.047), advanced TNM stage (HR = 4.941; 95% CI, 2.052–11.897; p  = 0.000), tumor invasion (HR = 3.472; 95% CI, 1.349–8.937; p  = 0.010), lymph node metastasis (HR = 8.846; 95% CI, 2.708–28.897; p  = 0.000), vascular invasion (HR = 3.237; 95% CI, 1.521–6.891; p  = 0.002), nervous invasion (HR = 2.324; 95% CI, 1.205–4.479; p  = 0.012), and CPNE1 expression (HR = 3.464; 95% CI, 1.440–8.334; p  = 0.006) were correlated with OS. In the multivariate analysis, age (HR = 2.514; 95% CI, 1.264–4.999; p  = 0.009), lymph node metastasis (HR = 8.441; 95% CI, 2.553–27.906; p  < 0.05), and CPNE1 expression (HR = 2.549; 95% CI, 1.051–6.186; p  = 0.039) were significant prognostic predictors for GC. Conclusions: Copines‐1 overexpression in GC is significantly associated with poor prognosis. Thus, CPNE1 levels may serve as a prognostic biomarker in GC patients. Abstract : Copines‐1 (CPNE1) is a soluble membrane‐binding protein that includes two tandem C2 domains at the N‐terminus and a C terminal A domain. Importantly, it is associated with the prognosis of various tumors, but there are only a few studies regarding the role of CPNE1 in gastric cancer. This study aimed to explore the clinicopathological significance and prognostic potential of CPNE1 in gastric cancer. Immunohistochemical analysis verified that CPNE1 was upregulated in gastric cancer tissue than ANT ( p  < 0.0001). Furthermore, CPNE1 was significantly associated with poor outcome both in public database ( p  = 9.4 e‐10) and clinical samples ( p  = 0.003). Thus, CPNE1 levels may serve as a prognostic biomarker in gastric cancer patients.